LANGUAGE LEARNING STRATEGIES BY INDONESIAN EFL LEARNERS: A CASE STUDY OF GENDER ROLE - Ajeng, Shonia (PEOPLE: International Journal of Social Sciences, 2017)
This research aimed to find out the language learning strategies used by English study program students and its differences between male and female ones. This study was a case study research, and the data were collected by using demographic background questionnaire and in-depth interviews with the selected participants.The findings were explained by using the theory of language learning strategies by O’Malley and Chamot (1990), in which they divided language learning strategies into metacognitive, cognitive and social/affective strategies.The results showed that there were differences between male and female learners in the use of language learning strategies in each language skill, but there were also similarities. Even though they have the same strategies, but they tend to have different activity in the learning process. The findings presented that male learners used more metacognitive and social strategies than female students, while female learners used more cognitive strategies than male. Cognitive strategies were the most frequently used strategies by both genders, and metacognitive are the least used one. The implication of this research for teaching and learning are the lecturer may get new knowledge, and ways of teaching and the students may find a new strategy to improve their language skills in language learning process.